The triglyceride-to-high density lipoprotein cholesterol ratio in overweight Korean children and adolescents - Dong-Yoon Yoo; Yu Sun Kang; Eun Byul Kwon; Eun-Gyong Yoo (Korean Society of Pediatric Endocrinology, 2017)
Purpose The triglyceride-to-high-density lipoprotein cholesterol (TG/HDL-C) ratio has recently been reported as a biomarker of cardiometabolic risk in obese children and adolescents. The purpose of this study is to describe the TG/HDL-C ratio and related factors in overweight and normal weight Korean children and to evaluate whether the high TG/HDL-C ratio is associated with insulin resistance in overweight children and adolescents. Methods Data from 255 overweight (aged 8.7±2.0 years) and 514 normal weight (aged 8.9±1.8 years) children and adolescents were evaluated. Glucose, insulin, total cholesterol (TC), HDL-C and TG levels were measured after overnight fasting, and the TG/HDL-C ratio, non-HDL-C and the homeostasis model assessment of insulin resistance (HOMA-IR) were calculated. Results The TG/HDL-C ratio was higher in overweight group compared to normal weight group (P<0.001). Among overweight children and adolescents, alanine aminotransferase (P=0.018), non-HDL-C (P<0.001), and HOMA-IR (P=0.004) were different between the TG/HDL-C ratio tertile groups. The prevalence of elevated HOMA-IR was increased with increasing TG/HDL-C ratio tertiles (P for trend=0.003). On regression analysis adjusted for age and sex, the BMI (β=0.402, P=0.001) and TG/HDL-C ratio (β=0.251, P=0.014) were independently associated with HOMA-IR (adjusted R2=0.324). The TG/HDL-C ratio of 2.0 or more showed higher sensitivity (55.6%) and specificity (72.9%), when compared to TC (≥200 mg/dL), non-HDL-C (≥145 mg/dL), and LDL-C (≥130 mg/dL) for identifying overweight children with elevated HOMA-IR. Conclusions The TG/HDL-C ratio is independently associated with insulin resistance in overweight children and adolescents, and it can be useful in identifying those at higher cardiometabolic risk.